The Comparison of Experience Quality between Domestic and Foreign Tourist: A Study on Sundanese Culture Performance in Bandung - Yuniasari Megandini; Lusianus Kusdibyo (Prosiding Industrial Research Workshop and National Seminar, 2018)
Nowadays, the tourism industry has grown so rapidly that it can become the driving force of a country's economy. For those many things that need to be improved in order to compete globally in the tourism context, one of them is to improve the experience quality of domestic and foreign tourists. Therefore, in this research, researcher wanta to know and examine in depth about the difference of experience quality between domestic and foreign tourists through its dimensions those are education, entertainment, peace of mind, and escapism. This study uses 359 tourists, who come to enjoy Sundanese cultural performance in Bandung as the object of research. The result of this study that is there are not differences in several dimensions of experience quality such as education, entertainment, and peace of mind. Meanwhile, the dimensions of escapism in the experience quality between foreign and domestic tourists is different.